2010
DOI: 10.1016/j.jtcvs.2009.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Selective endothelin-1 receptor type A inhibition in subjects undergoing cardiac surgery with preexisting left ventricular dysfunction: Influence on early postoperative hemodynamics

Abstract: Background and Objective A robust release of endothelin-1-1 (ET) with subsequent ETA subtype receptor (ET-AR) activation occurs in patients following cardiac surgery requiring cardiopulmonary bypass (CPB). Increased ET-AR activation has been identified in patients with poor LV function (reduced ejection fraction; EF). Accordingly, this study tested the hypothesis that a selective ET-AR antagonist (ET-ARA) administered peri-operatively would favorably affect post-CPB hemodynamic profiles in patients with a pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Our results in the vasopressin group-with normal ET A and ET B expression associated with normal jejunal microcirculation-are compatible with previous findings of a protective effect of ET receptor antagonists in ischemia/ reperfusion injury of the small bowel. 4,22 Additionally, a recent study by Toole and colleagues 23 proved the safety of ET A antagonist treatment in high-risk cardiac surgery patients. In line with this, the administration of ET-1 has been shown to result in reduced microvascular flow of the jejunum and ileum.…”
Section: Discussionmentioning
confidence: 97%
“…Our results in the vasopressin group-with normal ET A and ET B expression associated with normal jejunal microcirculation-are compatible with previous findings of a protective effect of ET receptor antagonists in ischemia/ reperfusion injury of the small bowel. 4,22 Additionally, a recent study by Toole and colleagues 23 proved the safety of ET A antagonist treatment in high-risk cardiac surgery patients. In line with this, the administration of ET-1 has been shown to result in reduced microvascular flow of the jejunum and ileum.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, cardiopulmonary bypass may have adverse effects on pulmonary vascular impedance. 95,96 Finally, postoperative invasive and even noninvasive positivepressure mechanical ventilation also have variable effects on pulmonary vascular impedance. 97,98 These arguments in favor of SE notwithstanding (particularly in critically ill patients such as those with massive PE), the optimal treatment of patients with lesser degrees of PE (ie, submassive or less) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were operated electively and the myocardium was protected with cardioplegia, reducing the peroperative ischemic insult. Thus it seems that AVR in AS patients does not lead to ET-1 augmentation during early reperfusion, contrary to reports from CABG operations where it has been demonstrated that plasma ET-1 levels are elevated after 30 min of reperfusion [32] and continue to rise during the reperfusion phase [8,9,18]. The lack of these findings in our study may be due to the short observational period early in the reperfusion phase (5–20 min), suggesting that ET-1 enters into circulating plasma at a later stage, or that cardiomyocyte and endothelial injury is attenuated during AVR due to a strict cardioprotective regime in the form of timely cardioplegia administration.…”
Section: Discussionmentioning
confidence: 75%
“…It is documented that ET-1 might affect postoperative outcome negatively in patients undergoing cardiac surgery [8,9,18]. Previous studies have reported that during cardiac surgery, the use of CPB leads to elevated plasma levels of ET-1 [19,20], and that levels remain elevated for 24 h [8,18]. Zhu et al [21] demonstrated that plasma ET-1 peaked after cessation of CPB in patients undergoing valvular surgery and correlated positively with bypass time.…”
Section: Discussionmentioning
confidence: 99%